Disharmonisasi Pasal 70 Undang-Undang Nomor 30 Tahun 1999 dengan Putusan Mahkamah Agung: Studi Putusan Mahkamah Agung Nomor 264 B/Pdt.Sus-Arbt/2014 - Khaira Nadila (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
In business activities, one of the most suitable alternative dispute resolution methods is arbitration. This research is conducted to understand and examine the principles of finality and binding nature as outlined in Article 70 of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Conceptually, arbitration relies on an arbitration agreement agreed upon by the disputing parties, and the District Court is not authorized to adjudicate the dispute. On the other hand, Law No. 30 of 1999 itself provides an opportunity for filing a cancellation appeal in court. To address this issue, the case study used is the Supreme Court Decision No. 264 B/Pdt.Sus-Arbt/2014. In this research, it was found that the non-absolute nature of the principle of finality and binding nature in arbitration is influenced by the need for executory power, which is the jurisdiction of the court, and the binding finality, although the opportunity is limited to reasons of null and void in the arbitration procedure. Although this principle is not absolute, the law does not automatically facilitate the cancellation requests filed. The non-absolute nature of the arbitration award principle in Law No. 30 of 1999 creates ambiguity regarding the principle of finality and binding nature, as in practice, parties who lose or feel that their interests are not accommodated seek ways to challenge the arbitration award, even with reasons beyond the provisions of Article 70 of Law No. 30 of 1999.